The Role of Islamic Religious Education Teachers in Fostering Students' Habit of Congregational Prayer - Azep Maulana; Mispani Mispani; Sunarto Sunarto (Assyfa Journal of Multidisciplinary Education, 2026)
This study aims to describe the role of Islamic Religious Education (PAI) teachers in fostering the habit of congregational prayer and to identify the supporting and inhibiting factors at SMPN 4 Abung Selatan, North Lampung. The background of this research is the low participation and consistency of students in performing congregational prayers at school. This study employed a qualitative approach with a case study type. Data collection techniques included participatory observation, in-depth interviews, and documentation. Research informants consisted of the school principal, PAI teachers, non-PAI teachers, and students. Data validity was ensured through source and technique triangulation as well as persistent observation. Data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results showed that the roles of PAI teachers include: (1) being role models in worship, (2) providing educative advice (mau'idhotul hasanah), (3) implementing educational sanctions, (4) individual approaches and spiritual guidance, and (5) creating a religious school environment. Supporting factors include adequate worship facilities, support from non-PAI teachers, enthusiasm of active students, and consistent habituation programs. Meanwhile, inhibiting factors are low worship awareness among some students, indiscipline in time management, and lack of effective supervision. In conclusion, the role of PAI teachers is central and multidimensional in shaping the habit of congregational prayer, but synergy between the school, teachers, and parents is needed to overcome existing obstacles.